1987
DOI: 10.1007/bf00218319
|View full text |Cite
|
Sign up to set email alerts
|

The projections of chemically identified nerve fibres in canine ileum

Abstract: The projections of nerve fibres with immunoreactivity for the peptides enkephalin (ENK), gastrin-releasing peptide (GRP), neuropeptide Y (NPY), somatostatin (SOM), substance P (SP) and vasoactive intestinal peptide (VIP) were studied in canine small intestine by analysing the consequences of lesions of intrinsic and extrinsic nerves. Of peptides present in fibres supplying myenteric ganglia, GRP, SOM and VIP were in anally directed nerve pathways, whereas ENK and NPY were in orally directed pathways. Pathways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
1

Year Published

1989
1989
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(29 citation statements)
references
References 26 publications
2
26
0
1
Order By: Relevance
“…In the guinea pig, both VIP and NPY neurons issue descending projections (c. f. FUR-NESS and COSTA, 1987), in the dog VIP neurons issue descending projections while NPY neurons issue ascending ones (DANIEL et al, 1987). It is also apparent that the structural organization and chemical coding of enteric neurons is not identical in all segments of the gut, as illustrated by our findings in the rat (see EKBLAD et al, 1987EKBLAD et al, , 1988.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…In the guinea pig, both VIP and NPY neurons issue descending projections (c. f. FUR-NESS and COSTA, 1987), in the dog VIP neurons issue descending projections while NPY neurons issue ascending ones (DANIEL et al, 1987). It is also apparent that the structural organization and chemical coding of enteric neurons is not identical in all segments of the gut, as illustrated by our findings in the rat (see EKBLAD et al, 1987EKBLAD et al, , 1988.…”
Section: Discussionmentioning
confidence: 73%
“…Rat Guinea-pig Dog guinea pig (c. f. FURNESS and COSTA, 1987) and dog (DANIEL et al, 1987), VIP and NPY seem to be stored in separate neurons. In the guinea pig, both VIP and NPY neurons issue descending projections (c. f. FUR-NESS and COSTA, 1987), in the dog VIP neurons issue descending projections while NPY neurons issue ascending ones (DANIEL et al, 1987).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…More-over, motor and sensory neurons are distinguishable electrophysiologically and some of their chemical characteristics have been established. The cell bodies of the motor neurons that supply the circular muscle coat are deduced to be in the myenteric plexus, because it has been shown that all nerve fibres of intrinsic origin that supply this layer come from the myenteric plexus in the guinea-pig small intestine (WILSON et al, 1987), and probably also in the dog small intestine (DANIEL et al, 1987). The longitudinal muscle of the guinea-pig small intestine is functionally innervated but it is not obvious from structural studies which fibres provide this innervation.…”
Section: Myenteric Plexus: Identification Of Motor and Sensory Neuronsmentioning
confidence: 99%